Circumpolar Information Tool Kit on Minerals, and Oil and Gas for Indigenous People and Northern Communities. Proposal submitted to the Arctic Council Sustainable Development Working Group. (Arctic Council Secretariat, 2007)
"The development of an information toolkit to increase Arctic Indigenous peoples’ and communities’ knowledge of the sustainable development of mineral and oil and gas resources. It will also strengthen their capacity to take advantage of potential opportunities offered and share the benefits of mining, oil and gas. This initiative will provide meaningful information for communities, governments and industries. The toolkit will feature easy-to-read descriptions of the activities related to the sustainable development of minerals and metals and oil and gas, and of impacts and opportunities for Arctic communities throughout the stages of the natural resources project cycle. It will be designed to: include explanations on the industry; its contributions to sustainable communities for current and future generations; the integration of environmental, social and economic considerations and the protection of traditional ways of life; and, address issues and problems common to both northern and indigenous peoples." /./